Rectourinary Fistula after Radical Prostatectomy: Review of the Literature for Incidence, Etiology, and Management - Hiroshi Kitamura; Taiji Tsukamoto (Prostate Cancer)
Although rectourinary fistula (RUF) after radical prostatectomy (RP) is rare, it is an important issue impairing the quality of life of patients. If the RUF does not spontaneously close after colostomy, surgical closure should be considered. However, there is no standard approach and no consensus in the literature. A National Center for Biotechnology Information (NVBI) PubMed search for relevant articles published between 1995 and December 2010 was performed using the medical subject headings “radical prostatectomy” and “fistula.” Articles relevant to the treatment of RUF were retained. RUF developed in 0.6% to 9% of patients after RP. Most cases required colostomy, but more than 50% of them needed surgical fistula closure thereafter. The York-Mason technique is the most common approach, and closure using a broad-based flap of rectal mucosa is recommended after excision of the RUF. New techniques using a sealant or glue are developing, but further successful reports are needed.